Rituximab for Rheumatoid Arthritis - Cohen, Marc D. (Rheumatol Ther, 2015)
Rituximab is a chimeric monoclonal antibody directed at the CD20 molecule on the surfaces of some but not all B cells. It depletes almost all peripheral B cells, but other niches of B cells are variably depleted, including synovium. Its mechanism of action in rheumatoid arthritis (RA) is only partially understood. Rituximab was efficacious in clinical trials of patients with RA, including those who are methotrexate naïve, those with an incomplete response to methotrexate, and those with an incomplete response to tumor necrosis factor inhibitors. The need for a concomitant traditional disease-modifying drug, the optimal dose of rituximab, and the optimal interval for retreatment remain somewhat uncertain. Rituximab seems to be most efficacious in seropositive patients and those with an incomplete response to only one tumor necrosis factor inhibitor. Rituximab has a reasonable safety profile, with a small risk of serious infectious events, which is stable over time and repeat courses. Opportunistic infections are rare. Reactivation of hepatitis B remains a concern. The possible association of rituximab and progressive multifocal leukoencephalopathy may still require vigilance. Malignancies and cardiovascular events do not appear to be increased. Infusion reactions are more likely with the initial infusion, and are usually mild. Rituximab may cause hypogammaglobulinemia, but any risk of subsequent risk of increased infectious events is not yet well established. Before initiating rituximab, patient screening for hypersensitivity to murine proteins, infections, congestive heart failure, pregnancy, and hypogammaglobulinemia is imperative. Vaccinations should be administered prior to treatment whenever possible. Rituximab has been a significant addition to the rheumatologists’ armamentarium for the treatment of RA.